Portrait of the Social Aspects of Curiak Island Buffer Village: Challenges and Opportunities in Community Empowerment - Abbas, Ersis Warmansyah; Koswara, Deden; Fahmanadie, Daddy; Ilhami, M. Ridha; Mursalin, Arisandy; Husna, Nur; Julia, Siti (Program Studi Pendidikan IPS, 2024)
This study aims to examine the objective condition of Anjir Serapat Muara village as one of the buffers of Curiak Island, with a focus on the social aspects of the local community. The method used in this study is a qualitative approach, including field observation, in-depth interviews, and secondary data analysis. The results of the study show that Anjir Serapat Muara village as a buffer for Curiak Island faces various challenges in social aspects, such as relatively low education levels and limited access to health services. This study concludes that integrated efforts are needed to improve the welfare of the community in the buffer village of Curiak Island, one of which is through community empowerment programs.